Pengaruh Ekuitas Merek Terhadap Minat Pembelian Pada Smartphone Asus (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta ) - Bharata, Basic Exwan; , Dr. Kussudyarsana, S.E., M.Si (2016)
This study aims to determine: the effect of brand equity that include brand awareness, brand association, perceived quality, and brand loyalty to purchase intention of Asus smartphone in the students of the Faculty of Economics and Business, University of Muhammadiyah Surakarta, both individually and together. The type of this study was a quantitative study. The population in this study were all students at the Faculty of Economics and Business, University of Muhammadiyah Surakarta. The sampling technique uses simple random sampling method with a sample size of 100 respondents . Data obtained from the results of the questionnaire , with Likert scale 1-5 . The data analysis method used : (1) The validity and reliability test . (2) The classical assumption test, consisting of normality, multicollinearity and heteroscedasticity test. (3) Multiple linear regression test, and (4) Hypothesis testwhich consists of t test , F test and R2test. Results of data analysis obtained the following results : (1) brand awareness, brand association, perceived quality, and brand loyalty individually had apositive and significant effect on the purchase intention. (2) brand awareness, brand association, perceived quality, and brand loyalty simultaneously had positive and significant effect on the purchase intention. (3) the test results in this study obtained R2 value of 80.9 %, while the remaining 19.1% is influenced by other factors not included in this research model.